(3QSGdI GdeYGfi dgQeS GdMcje GdaGVds - (3gQeS GdMcjes
(3ChdgG (B:s
(3GdeKdK GdMceI ai eYGfi GdfaS hQLhYgG Yf GdCehQ GdTcdjI hNUgG Ydi WdH eG jdGFegG hjTGWgG ef GdCehQ GdYdhjI hbUQgG Ydi eG jhQOgG s
(3BNQgG (B:s
(3hEf KeQI GdYed GdUGdM cCUdgG hKeQI GdYed GdQOF cCUdgG hbdjd ef GdYde eY GdYed CfaY ef cKjQ ef GdYde eY bdg GdYed cedJ GdQSGdI GdQGHYI YTQ dgQeS GdMcje hGdMeO ddg Edi CHO GdOghQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs